2017
DOI: 10.1016/j.fishres.2016.11.010
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of fully documented fisheries to estimate discards in a participatory research scheme

Abstract: a b s t r a c tA key challenge for fisheries science and management is the access to reliable and verifiable catch data. In science, the challenge is to collect reliable, precise and traceable data to provide sound advice. In management, the challenge is that catch documentation is necessary to enforce regulations. Currently, catch inspection at sea, self-reporting through e-log and on-board observers are the primary methods to document catches at sea. However, at-sea control and on-board observers are costly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 10 publications
(24 reference statements)
1
8
0
Order By: Relevance
“…Onboard observers is currently the only MCS tool which can attain the same coverage level as EM and in fact for some metrics, such as age and mass estimates, allow for higher quality data than EM (Gilman et al, 2019;James et al, 2019). However, as other papers concerning EM with video have previously stated, the running costs of fisheries control with EM is lower than a similar coverage obtained with on-board observers and issues like observer safety at-sea and space limitations for an extra person on a vessel must also be taken into account (Gilman et al, 2019;James et al, 2019;Kindt-Larsen et al, 2011;Mangi et al, 2015;Mortensen et al, 2017;Needle et al, 2015).…”
Section: Alternative Compliance Measuresmentioning
confidence: 86%
See 3 more Smart Citations
“…Onboard observers is currently the only MCS tool which can attain the same coverage level as EM and in fact for some metrics, such as age and mass estimates, allow for higher quality data than EM (Gilman et al, 2019;James et al, 2019). However, as other papers concerning EM with video have previously stated, the running costs of fisheries control with EM is lower than a similar coverage obtained with on-board observers and issues like observer safety at-sea and space limitations for an extra person on a vessel must also be taken into account (Gilman et al, 2019;James et al, 2019;Kindt-Larsen et al, 2011;Mangi et al, 2015;Mortensen et al, 2017;Needle et al, 2015).…”
Section: Alternative Compliance Measuresmentioning
confidence: 86%
“…The inclusion of hake is not possible to discern in the audit time but the change to a more precise length measurement increased the needed audit time. Another example is that Mortensen et al (2017) reported an average of 41 min per haul used for video audit, whereas the CCQM had an average audit time of 21 min per haul for vessels with conveyor belt and 38 min for vessels without conveyor belt in the last year of the trial. The two trials had similar vessel composition and the EM system applied was the same but the trial conducted by Mortensen et al (2017) also audited discards of plaice (Pleuronectes platessa) and Nephrops (Nephrops norvegicus) in addition to cod, saithe, hake, haddock and whiting.…”
Section: Cost Of Em With Videomentioning
confidence: 99%
See 2 more Smart Citations
“…This includes understanding the mechanistic aspects of their gear's performance, but also an awareness of the behavioural responses of the species caught (Diaz Pauli and Sih, 2017;O'Neill et al, 2019). In recent years, most industry-science collaborations in Europe have taken such a bottom-up approach (Armstrong et al, 2013;Mortensen et al, 2017), and a number of gears such as the netting grids in the Scottish Nephrops fishery (Drewery et al, 2012;Kynoch et al, 2012) have been successfully introduced. Likewise, fishers' local ecological knowledge together with scientifically based mapping programs of areas with high presence of juveniles (Reid et al, 2019) is equally necessary for the development of spatial and temporal closure management systems and to design sustainable strategies on where, when and how to fish (Dunn et al, 2011;Rijnsdorp et al, 2012).…”
Section: Improving Gear Selectivitymentioning
confidence: 99%